The Effect of Bladder Outlet Obstruction on Bladder Cancer Recurrence and Progression - Utku Can; Erdinç Dinçer; Alper Coşkun; Cengiz Çanakçı; Fehmi Narter (Journal of Urological Surgery, 2025)
Objective: To investigate the effect of bladder outlet obstruction (BOO) on cancer recurrence and progression in patients with non-muscle invasive bladder cancer (NMIBC). Materials and Methods: A retrospective analysis was conducted on 256 male patients diagnosed with primary NMIBC at Kartal Dr. Lütfi Kırdar City Hospital between 2010 and 2018. Patients were divided into two groups according to the presence of BOO (BOO group, n=123; control group, n=133). Demographic and pathological data, as well as intravesical treatments, recurrence and progression status of both groups were recorded and compared according to cystoscopy findings in five years of follow-up. Results: Patients with BOO were older and had higher rates of comorbidities, larger prostate volumes, higher prostate-specific antigen levels, and more frequent cystoscopic findings of trabeculation and diverticula (p<0.001). Initial pathology showed higher rates of T1 stage and high-grade tumors in the BOO group (50% vs. 24%, p=0.003 and 42.6% vs. 21%, p=0.008, respectively). A multivariate logistic regression model indicated that BOO was not an independent variable to predict any initial bladder cancer pathology, recurrence, or progression rate (p>0.05). The presence of trabeculation in cystoscopy was found to be an independent predictor of the initial diagnosis of high-grade/carcinoma in situ urothelial carcinoma, with an odds ratio of 4.62 (95% confidence interval, 1.3-17; p=0.021), following adjustment for potential confounding variables. Conclusion: Findings of this study indicate that BOO does not affect disease recurrence or progression, nor does it affect the pathological features of the tumour at the time of diagnosis. Conversely, increased bladder trabeculation resulting from BOO may be associated with a higher-grade tumor at the time of initial diagnosis.